2021
DOI: 10.1177/21582440211004163
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Cardiovascular Disease Prevention Behavior Among Office Workers Based on an Ecological Model

Abstract: The purpose of this study was to investigate the personal, interpersonal, and organizational factors associated with cardiovascular disease (CVD) prevention behavior among office workers using an ecological model. A total of 221 office workers working in areas such as personnel, design, and accounting, and who work in offices, completed the survey. Health Perception Questionnaire, General Self-Efficacy Scale (GSE), Multidimensional Scale of Perceived Social Support (MSPSS) Scale, the Korean Occupational Stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Further, in our study, higher culture of health scores was associated with lower stress and depression scores, consistent with results from previous studies. Kwon and Marzec [23] and Pahn and Yang [40] both observed significant associations between workplace culture of health and occupational stress in their respective studies. With regard to mental health, Jia and colleagues [22] found that workplace culture of health was positively related to mental health and happiness.…”
Section: Discussionmentioning
confidence: 93%
“…Further, in our study, higher culture of health scores was associated with lower stress and depression scores, consistent with results from previous studies. Kwon and Marzec [23] and Pahn and Yang [40] both observed significant associations between workplace culture of health and occupational stress in their respective studies. With regard to mental health, Jia and colleagues [22] found that workplace culture of health was positively related to mental health and happiness.…”
Section: Discussionmentioning
confidence: 93%
“…Designing atriums and larger daylight channels (Candido et al, 2019) provides employees with more natural light. Regarding the social environment, employee behaviors are affected by interpersonal relationships, such as with family, friends, and colleagues (Pahn and Yang, 2021) on the one hand and are intervened by the management system of the company and the organization (Maphong et al, 2022) on the other. These strategies will encourage employees to reduce sedentary activity and strengthen physical activity, such as the elimination of desk ownership and the implementation of a workstation rotation system (Candido et al, 2019), the prohibition of bringing food into the workstation, the encouragement of walking out to eat (De Cocker et al, 2015), the use of online mini programs to conduct employee clock-in activities, and regular step log feedback (Zhang et al, 2015;Iyengar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%